Application of problem tree analysis (PTA) and logic model in conceptualising post conservation evaluation (PCE) for heritage building maintenance in Malaysia - Wong Lai Kee; Muhammad Firzan bin Abdul Aziz (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
A theoretical gap in the area of conservation management in terms of leveraging evaluation practice to built heritage conservation has been identified. Sensitising this shortage, review made in this conceptual paper is basically to introduce Post Conservation Evaluation (PCE) devoted to evaluate maintenance at public heritage museums in the UNESCO Historic Cities of the Straits of Malacca aiming in developing and integrating the agenda of evaluation in the existing local conservation framework. Accordingly, elaboration of maintenance as the PCE subject of concern and the pertaining theories within evaluation field will be provided herein. In particular, this paper will present on document analysis made on the Draft of Special Area Plan (SAP) of Melaka and George Town, through the employment of Problem Tree Analysis (PTA) in the quest to identify on the causal, core, and consequent problems affecting built heritage conservation within the research locale. Finally, the use of Logic Model as a conceptual framework will be demonstrated to derive on strategies required prior developing PCE measures.